Change detection and deformation monitoring of concrete structures using terrestrial laser scanning - Mukupa, Wallace (2017)
Concrete structures are routinely monitored to detect change and deformation in the field of engineering surveying and other overlapping disciplines such as civil and structural engineering. The monitoring of civil infrastructure is crucial to the safe operation and the longevity of the system. There is growing demand for the development of reliable non-destructive testing techniques for concrete structures in the assessment of the deteriorating condition of infrastructures or in an event of fire-damaged structures. This research investigated the use of terrestrial laser scanning (TLS) for structural health monitoring and the implemented workflow is designed for non full-waveform laser scanner data. Although the use of TLS is not new within the domain of structural health monitoring, the novelty of this research lies in the application of the technology in the specific area of assessing fire-damaged concrete on one hand and the assessment of robust point cloud processing algorithms for precise structural deformation analysis on the other hand.